Cloning of Copper resistance gene (copA) that Presence in Novel Genomic Island of Acinetobacter baumannii A92 - Saad, Suhad; Melconian, Alice; hiah, Ali (Iraqi Journal of Science, 2023)
This study was aimed to detect weather copA gene(copper resistance gene ) presence in A.baumannii A92 genome(AbaR genomic islands). The full genomic sequence of A.baumannii A92 not published in NCBI genome similarity was detected between two strains so the sequence of A.baumanniiIS-116(Genebank-AMGF0100000.1 ) was used to design the primers that were used for amplify of copA gene of A.baumannii A92.Two primers contain two sites for restriction enzymes (KpnI,XohI) and PWSK29 vector were used in the cloning, double digestion has been performed for vector and gene. Then the re-ligation was completed to form recombinant molecule,after that, transformation have been performed for the recombinant molecule by using chemical competent E.coli DH5α. Finally ,the transformant cells were incubated for 16-18hr at 37°C, the white positive colony that contain recombinant vector was appeared .After that, the success of cloning was confirmed by using colony PCR method for white colony by using copA-F with M13-R(universal primer) primers ,the results of colony PCR confirmed the presence of insert gene by appearing of inserted band.